2013
DOI: 10.1161/atvbaha.112.301019
|View full text |Cite|
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ Coactivator-1α Is a Central Negative Regulator of Vascular Senescence

Abstract: Objective Cellular senescence influences organismal aging and increases predisposition to age-related diseases, in particular cardiovascular disease, a leading cause of death and disability worldwide. PGC-1α is a master regulator of mitochondrial biogenesis and function, oxidative stress and insulin resistance. Senescence is associated with telomere and mitochondrial dysfunction and oxidative stress, inferring a potential causal role of PGC-1α in senescence pathogenesis. Methods and Results We generated a PG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 47 publications
2
75
0
Order By: Relevance
“…SIRT1, as an important class III histone deacetylase, participates in many cell functions, i.e., senescence, proliferation, differentiation, and apoptosis [2,29,30]. It has been shown that mammalian SIRT1 is involved in chromatin remodeling, gene silencing, DNA damage response [31], and caloric restriction [32].…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1, as an important class III histone deacetylase, participates in many cell functions, i.e., senescence, proliferation, differentiation, and apoptosis [2,29,30]. It has been shown that mammalian SIRT1 is involved in chromatin remodeling, gene silencing, DNA damage response [31], and caloric restriction [32].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis, defined as programmed cell death, also serves a homeostasis function through the regulation of cell death upon stress [7.] Senescence also contributes to the development of diabetic complications and age-related diseases [8]. There are complex relationships within autophagy, apoptosis and senescence.…”
Section: Introductionmentioning
confidence: 99%
“…Disrupting RAS has been shown to provide significant benefit for cellular function, and this effect has been shown to be reliant on mitochondrial-ROS [12,13,14,15]. Angiotensin II (Ang) exposure or overexpression of Ang type 1 receptor (AGTR1)-coupled-G-protein, Gaq, induces excessive ROS production and triggers autophagy, senescence and apoptosis in cardiomyocytes and smooth muscle cells [8,16,17]. However, whether RAS activity is increased and whether there is benefit to the use of angiotensin-converting enzyme inhibitors (ACEIs) or angiotensin II type 1 receptor blockers (ARBs) in diabetic patients without cardiovascular complications remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In mice lacking telomerase, up to 4 generations may be required for such effects to be observed [3]. However, even in mice, shortened telomeres arise and characterize certain pathologies, such as atherosclerosis [4]. Telomeres of humans are significantly shorter than in mice: on the one hand it is thought that short telomeres may contribute to aging-related immune dysfunction, but on the other hand protect humans from cancer [5].…”
Section: Introductionmentioning
confidence: 99%
“…This effect results in more severe atherosclerosis, as well as vascular senescence characterized by reduced TERT, SIRT1 and catalase, as well as increased p53 expression. Thus PGC-1a may play a key role in preventing vascular senescence and atherosclerosis [4].…”
Section: Introductionmentioning
confidence: 99%